1987
DOI: 10.1002/jobm.3620270106
|View full text |Cite
|
Sign up to set email alerts
|

Differences in enzyme activities of Lipomyces starkeyi between cells accumulating lipid and proliferating cells

Abstract: Differences in intracellular enzyme activities between cells accumulating lipid and proliferating cells were studied with Lipomyces starkeyi, a fat-producing yeast. When the cells were removed from a medium for lipid accumulation t o a medium for cell proliferation, activities of several enzymes on the glycolytic pathway, pentosephosphate cycle, glycerol 3-phosphate pathway, tricarboxylic acid cycle and fatty-acid biosynthesis pathway changed. In the proliferating cells, activities of glycerol-3-phosphate dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This is similar to the recent report by Naganuma et al (1987) for L. starkeyi that ACL activity was also high during lipid accumulation but greatly reduced during cell proliferation. ACL is inhibited by fatty acyl-CoA esters (Boulton & Ratledge, 1983a, b), which are the first breakdown products of triacylglycerol degradation; although this could bring about the rapid cessation of enzyme activity, on mixing of extracts from both types of cell (triolein grown and nitrogenlimited) the resultant specific activity was approximately half the individual activities.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to the recent report by Naganuma et al (1987) for L. starkeyi that ACL activity was also high during lipid accumulation but greatly reduced during cell proliferation. ACL is inhibited by fatty acyl-CoA esters (Boulton & Ratledge, 1983a, b), which are the first breakdown products of triacylglycerol degradation; although this could bring about the rapid cessation of enzyme activity, on mixing of extracts from both types of cell (triolein grown and nitrogenlimited) the resultant specific activity was approximately half the individual activities.…”
Section: Discussionsupporting
confidence: 92%
“…This result suggests that both the lipid-accumulation ability and the strength of the fat globule membrane could affect TAG recovery. The glycolytic pathway, pentose phosphate cycle, glycerol 3-phosphate pathway, tricarboxylic acid cycle, fattyacid biosynthesis pathway, and carbon uptake are involved in TAG biosynthesis in cells, and different enzymes regulate these pathways (Hübscher, 1970;Naganuma et al, 1987;Wakil, 1970). It is suggested that the high lipid accumulation is induced by the activation of these pathways Yeast strains corresponding to renewable resources as carbon sources.…”
Section: Characteristics Of Strains With a High Lipid Accumulationmentioning
confidence: 99%